2020
DOI: 10.3390/mps3010021
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid and High Throughput MIC Determination Method to Screen Uranium Resistant Microorganisms

Abstract: The assessment of minimum inhibitory concentration (MIC) is a conventional technique used for the screening of microbial resistance against antibiotics, biocides, and contaminants such as heavy metals. However, as part of our ongoing work, we have observed biases associated with using traditional liquid MIC method to screen microbial heavy metal resistance, including both bacterial and fungal strains. Specifically, the addition of uranium into synthetic media causes immediate precipitation prior to the initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Despite this advantage of microbially based heavy metal bioremediation, studies have also unequivocally shown that bacteria can acquire antibiotic resistance when exposed to long-term contamination, especially with Hg and U ( Benyehuda et al, 2003 ), including our previous work ( Agarwal et al, 2019 , 2020a , b ; Gendy et al, 2020a , b ; Pathak et al, 2020 ). This builds upon significant evidence that exists on the SRS soils which unequivocally shows higher levels of antibiotic resistance in contaminated SRS soils relative to reference soils ( Stepanauskas et al, 2006 ; Wright et al, 2006 ; Thomas et al, 2020 ).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Despite this advantage of microbially based heavy metal bioremediation, studies have also unequivocally shown that bacteria can acquire antibiotic resistance when exposed to long-term contamination, especially with Hg and U ( Benyehuda et al, 2003 ), including our previous work ( Agarwal et al, 2019 , 2020a , b ; Gendy et al, 2020a , b ; Pathak et al, 2020 ). This builds upon significant evidence that exists on the SRS soils which unequivocally shows higher levels of antibiotic resistance in contaminated SRS soils relative to reference soils ( Stepanauskas et al, 2006 ; Wright et al, 2006 ; Thomas et al, 2020 ).…”
Section: Introductionmentioning
confidence: 84%
“…Our ongoing culture-dependent and culture-independent work on the SRS metalliferous soils has demonstrated several different bacterial groups involved in metal cycling processes, such as Arthrobacter spp., Burkholderia spp., Bacillus spp., Bradyrhizobium spp., Pseudomonas spp., Lysinibacillus spp., Paenibacillus spp., Stenotrophomonas spp., and Serratia spp. ( Agarwal et al, 2020a , b ; Gendy et al, 2020b ). Many of these groups have been demonstrated to cycle Hg by activity of their mer operon, which consists of regulatory proteins- MerR and MerD, transport proteins- MerP, T and E, as well as protein(s) with reductase activity- MerA ( Agarwal et al, 2019 ; Pathak et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Soil samples for this study were collected from metalliferous SRS 101 (33°19′02.1ʺN, 81°42′54.0ʺW) and shipped overnight on ice to the Florida A&M University (FAMU) laboratory. Soil was homogenized, serially diluted, and plated on lysogeny broth (LB) agar, Bradyrhizobium selective medium (BJSM), and potato dextrose agar (PDA) supplemented with U (2 mM) in the form of uranyl nitrate, followed by incubation at 30°C, as reported previously ( 6 ). Colonies with variable morphologies were selected and streaked onto 2 mM U to obtain isolated colonies.…”
Section: Announcementmentioning
confidence: 99%
“…Isolated strains were frozen in a solution of autoclaved 15% glycerol and preserved at −80°C. DNA was extracted from the isolates using the ZR fungal/bacterial DNA kit (Zymo Research, Irvine, CA, USA) and identified using 16S rRNA and 18S rRNA gene sequencing, as shown before ( 6 ). The obtained 16S and 18S rRNA gene sequences were analyzed using NCBI BLAST, and details are presented in Table 1 .…”
Section: Announcementmentioning
confidence: 99%
See 1 more Smart Citation